Problem Based Learning (PBL) Model for Science Material on Prevention of Dengue Fever for Elementary School - Laila Fajrin Rauf; Sigit Prasetyo (BASICA, 2025)
Dengue fever is very common in Indonesia. In June 2024, there will be 119.709 cases with a deadth rate of 777 cases. Most of the spread occurs in schools, so learning about dengue fever is very important. This research aims to provide the concept of a problem based learning model to explain dengue fever lessons to students. The type of research used is descriptive qualitative. The results of this research are (1) Many students do not have comprehensive knowledge about dengue fever (2) The learning process about dengue fever is still carried out conventionally, namely by reading textbooks at school so that students do not have direct experience in preventing the spread of dengue fever mosquitoes (3) The problem based learning model provides a solution for explaning dengue fever in schools. This model invites students to solve problems and trains students to think critically. In problem based learning there are five syntaxes carried out by the teacher. Of the five syntaxes, there are three main steps, namely learning preconditions, core learning agenda and post-learning. Students are invited to actively search for information, observe, process data until they are able to provide conclusions about the dengue fever problem they are facing.